PENGEMBANGAN MEDIA PEMBELAJARAN K3 BERBASIS ANDROID SEBAGAI STRATEGI EDUKATIF UNTUK MELATIH SISWA SMK SEBAGAI TENAGA KERJA TERAMPIL DI PASAR GLOBAL - Yusron Mubarok (Jurnal Pendidikan Vokasi Otomotif, 2019)
This research aimed to (1) identify the type of android-based learning media suitable for the vocational school’s students, (2) develop android-based learning media, and (3) validate the android-based learning media. This study is a Research and Development (RD) adapted from Sugiyono’s Model. It took place in a Public Vocational High School in Purbalingga. Research data were collected using questioner dan analysed using descriptive analysis. The result showed that: (1) the identifed of learning media necessary were (a) font “Times New Roman”, (b) font size “15 pt”, (c) font colour “following Background”, (d) align text “justify”, (e) picture orientation “above”, (f) background colour “blue”, (g) button tittle “text”, (h) button animation “moving”, (i) backsound “Off”, (j) button sound effect “Click”. There were seven steps of (2) developing learing media, they are  (a) designing product, (b) Collecting product’s source, (c) creating product, (d) validating product, (e) revising I, (f) testing product, (g) revising II. The (3) learning media was categorized “very good” meant that this media learning was valid to used.